Di antara Pusaran Gelombang Korea - Eka Wenats Wuryanta (Ultimacomm: Jurnal Ilmu Komunikasi, 2011)
Globalization is a special phenomenon in human civilization that moves on the global community and is part of the global human processes. The presence of information and communication technologies to accelerate the globalization of this. Globalization touches all the important aspects of life. Globalization creates new challenges and problems that must be answered, solved in an effort to harness globalization for the benefit of life. In general, globalization means the increasing linkages between the people and places as a result of advances in transportation technology, communications, and information that led to the convergence of political, economic, and cultural. The discourse of globalization as a process characterized by the rapid development of science and technology so that it can fundamentally change the world. International transport and communications have removed the boundaries of each nation’s culture. Marshall McLuhan’s global village pioneer idea in his book Understanding Media, 1964 said: “Today, after more than a century of electrictechnology, we have extended our central nervous system itself in a global embrace, abolishing both space and time as far as our planet is concerned. “ Key word: Globalisasi, Gelombang Korea, Media Televisi, K-Pop, informasi dan Komunikasi